Thiahelicene-based inherently chiral films for enantioselective electroanalysis - Arnaboldi, Serena (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
Chiral electroanalysis could be regarded as the highest recognition degree in electrochemical sensing, implying the ability to discriminate between specular images of an electroactive molecule, particularly in terms of significant peak potential difference. A groundbreaking strategy was recently proposed, based on the use of “inherently chiral” molecular selectors, with chirality and key functional properties originating from the same structural element. Large differences in peak potentials have been observed for the enantiomers of different chiral molecules, also of applicative interest, using different selectors, all of them based on atropisomeric biheteroaromatic scaffolds of axial stereogenicity. However, helicene systems also provide inherently chiral building blocks with attractive features. In this paper the enantiodiscrimination performances of enantiopure inherently chiral films obtained by electrooxidation of a thiahelicene monomer with helicoidal stereogenicity are presented for the first time. The outstanding potentialities of this novel approach are evaluated towards chiral probes with different chemical nature and bulkiness, in comparison with a representative case of the so far exploited class of inherently chiral selectors with axial stereogenicity. It is also verified that the high enantiodiscrimination ability holds as well for electron spins, as for atropisomeric selectors.